Indonesian Islamic Banking In Mastering The Global Halal Value Chain: Opportunities And Challenges From Economics And Legal Aspects - Widuhung, Sisca Debyola; Machmud, Aris (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Islamic banking has the ability to survive (durable) in times of crisis, has competitiveness and is efficient in improving the national economy. The commercial aspect of the economy can be seen from the existence of the financial services sector and the halal industry, while in the legal aspect, Indonesia has legal pluralism - the customary law system, the Islamic legal system and the western legal system. The formulation of the problem is How are the steps and strategies for Indonesia so that Indonesian Islamic Banking becomes a leader in the world halal value chain? The method used in this research is normative juridical with quantitative analysis approach. The conclusion of this study is that the position of Islamic banks in the economic system and national legal system has a strong position to become a Muslim country to become a leader in the development of the world Islamic financial market and global halal value chain by utilizing regulatory and policy support that supports the development of a halal value-based economy and Islamic banking and support the development of the world’s halal industry that meets the expectations of the community